Family Partnership Intervention to Improve Independence and Glycemic Control in Elderly with Type 2 Diabetes: Pre-Experimental Study - Sasmiyanto Sasmiyanto; Dian Ratna Elmaghfuroh (Universitas Tribhuwana Tunggadewi, 2026)
Type 2 diabetes mellitus is a prevalent chronic condition among the elderly that contributes not only to physiological complications but also to decreased independence in daily activities. This study aimed to analyze the effectiveness of a family partnership–based intervention in improving independence and glycemic control among elderly individuals with type 2 diabetes mellitus. A pre-experimental one-group pre–posttest design was employed involving 64 elderly participants selected through stratified random sampling in a community setting in Bondowoso, Indonesia. Data were collected using the Barthel Index to assess independence and random blood glucose measurements using a calibrated glucometer to evaluate glycemic control. Univariate analysis was used to describe the data, while the Wilcoxon signed-rank test was applied to determine differences before and after the intervention. The results showed a decrease in mean glycemic levels from 169.14 to 135.56 and a shift in independence levels, with a higher proportion of participants classified as having mild dependency after the intervention. Statistical analysis indicated a significant difference in independence levels (p 0.05). These findings demonstrate that a family-centered partnership approach effectively improves both functional independence and glycemic control among elderly individuals with type 2 diabetes mellitus. The intervention promotes active involvement of both elderly individuals and caregivers, enhances self-efficacy, and reduces dependency. This model provides a practical and culturally adaptable strategy for community-based chronic disease management and highlights the importance of family engagement in improving health outcomes among the elderly.